Middle Jurassic isolated dinosaur tracks from Msemrir (Central High Atlas, Morocco): Evidence for theropod occurrence and paleogeographic distribution - Noura Lkebir; Yao-Yan He; Xiong-Wei Zeng; Cheng-Gang Wang; Fa-Fu Wu; Lai-Shi Zhao; Zhi-Jun Niu (Palaeoworld, 2026)

Engineering a robust glucose oxidase: Enhanced thermostability, acid tolerance and catalytic activity drive high-level gluconic acid production - Ying-Zhi Peng; Xin-Cheng Jiang; Jing Li; Yi-Fa Yu; Jia-Yu He; Bing-Yan Xu; Xiang Lv; Qiong-Ying Wu; Shuai You; Jun Wang (Food Chemistry, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Asymmetric coordination configuration unlocks single-atom nanozyme catalytic activity for redox-immune homeostasis and temporomandibular joint osteoarthritis therapy via macrophage depolarization and cGAS-STING pathway inhibition - Kaixun He; Hanyu Lin; Penghui Wei; Hongjia Zheng; Zhonghan Chen; Sihui Zhang; Yanjing Ou; Wenting Jiang; Wenxiu Yuan; Geyuan Zheng; Jiang Chen; Yi Zuo; et al. (Chemical Engineering Journal, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Physiological and transcriptomic analyses reveal the effect of exogenous chitosan oligosaccharides on ‘Harumi’ fruit resistance to Penicillium digitatum - Mingfei Zhang; Xu Zou; Jiahuan Liu; Yuping Wang; Yuming Ren; Bin Peng; Huan Liu; Fa He; Bo Xiong; Ling Liao; Siya He; Guochao Sun; et al. (Food Control, 2026)

Construction of a GdVO4-In2O3 n-n heterojunction enables ppb level triethylamine detection at low temperatures - Yi-Cheng Geng; Xiang-Bing Li; An-Qi Wang; Bing-Yi Xi; Qian-Qian Zhang; Li-He Yan; Fa-Ming Li; Wei-Dong Zhu (Chemical Engineering Journal, 2026)

Pioglitazone (PIO) enhances blastocyst vitrification outcomes via coordinated AQP3-mediated dehydration and antioxidant defense - Kai-Yan Zhang; Cai-Yu Wang; Jing Guo; Chang-Guo Min; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; Yang Lyu; Dian Wang; Xin Ma; et al. (Theriogenology, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

Salt barriers produce optimal effects in increasing crop yield and reducing salinity in semi-arid and coastal areas compared to other regions: A meta-analysis - Lang Liu; Fang Kang; Jing Xu; Zhen Liu; Huarui Gong; Ziyang He; Keyu Fa (Field Crops Research, 2026)

Ophiocordyceps polystromata , a new entomopathogenic fungus from the Gaoligong Mountains in western Yunnan, China - He-Fa Liao; Ping-Ping Su; Ze-Mei Chen; Luo-Dong Huang; Qi Fan; Qiu-Lu Yang; Zhu-Liang Yang; Wei-Hong Hu; Yuan-Bing Wang (New Zealand Journal of Botany, 2025)

Multigraph fusion neural network for predicting available cadmium levels in farmland soils - Ren-Jie Zhang; Shu-Fang Pan; Huai-Zeng Xing; Tian-Hao Dong; Sai-Hua Liu; Tao Xue; Fa-Xiang Tian; Hong-Yu Fu; Yun-He Xie; Xiong-Hui Ji (Environmental Pollution, 2025)

Environmental preferences and interspecific interactions of autotrophic microorganisms in dryland agroecosystems soils - Boyuan Liu; Fang Kang; Zicun Zheng; Lang Liu; Jing Xu; Ziyang He; Keyu Fa (Applied Soil Ecology, 2025)

A novel dual co-catalyst strategy using MXene and NCDs for boosting TiO2 photocatalytic efficiency under visible light - Caixia Li; Yuyang Chen; Fangyun Zhou; Suxiang Ge; Wenjun Fa; Weiwei He (Journal of Environmental Chemical Engineering, 2025)

Furosemide sodium enhanced AQP3 expression by inhibiting NKCC1 leading to improved vitrification freezing rates of mouse and bovine blastocysts - Chang-Guo Min; Xue-Song Shan; Kai-Yan Zhang; Yu-Chan Wang; Xin Ma; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; Dian Wang; Jing Guo; et al. (Theriogenology, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Investigation on the influence of droplets on the flow characteristics and energy separation in vortex tube based on CFD analysis - Lijuan He; Zhong Zhou; Zhi Li; Jianzi Yang; Fa Zhang; Xingyu Meng; Wenxi You; Chenlei Zhao (International Journal of Refrigeration, 2025)

Effects of years of storage (1, 5, and 7 years) on bovine sperm ultrastructure, oxidative status, and fertilizing capacity - Chang-Guo Min; Si-Min Wang; Zhi-Le Fan; Kai-Yan Zhang; Sheng-Kui Hou; Xin-Hai Wang; Xin Ma; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; et al. (Cryobiology, 2025)

Facilely prepared N-modified carbon quantum dots as microalgal photosynthesis promoters for wastewater treatment - Fa-wen Liang; Jing-Yuan Chen; Jun-liang He; Zhang Liu; Wei-cheng Xu; Yu-jun Huang; Xin-Di Liao; Si-Cheng Xing (Journal of Environmental Management, 2025)

Self-adaptive graph neural network for predicting blast-induced damage in RC columns across multiple scenarios - Jiang-Zhou Peng; Liu-Juan Pan; Zhi-Qiao Wang; Guang-fa Gao; Mingyang Wang; Jie Hu; Yong He; Wei-Tao Wu (Engineering Structures, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Associations of exposure to arsenic species and endogenous sex hormones with oral cancer: a hospital-based study in Southeastern China - Na Wang; Wenting Zhang; Haoyuan Song; Weihai Huang; Fa Chen; Fengqiong Liu; Yulan Lin; Yu Qiu; Bin Shi; Lisong Lin; Jing Wang; Baochang He (Environmental Pollution, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Research on Construction of combined model weighting function and its application on aeromagnetic 3D inversion modeling - Xiu-he Gao; Sheng-qing Xiong; Si-yuan Sun; Zhao-fa Zeng; Chang-chun Yu (Applied Geophysics, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Magnitude, distribution and temporal trend of nitrous oxide emissions from China’s natural soils over 1980–2022 - Songbai Hong; Zimeng Li; Mingsong Tang; Fa Li; Yitong Yao; Yanzi Yan; Mingzhu He; Xuhui Wang; Hui Zeng; Shilong Piao (Science China Earth Sciences, 2025)

Multiscale progressive 3D geological modeling based on isochronous stratigraphy identification in urban underground space - You Zhang; Ling-Ling He; Yu-Yong Jiao; Han-Fa Peng; Shun-Chang Liu; Qian-Bing Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

The Role of SIRT1–BDNF Signaling Pathway in Fluoride-Induced Toxicity for Glial BV-2 Cells - Bo Yang; Feiqing Wang; Xu Yang; Xiaoshuang Yuan; Yuting Yang; Xiaoxu Chen; Tingting Tian; Fa Chen; Dongxin Tang; Zhixu He; Yang Liu; Yanju Li (Biological Trace Element Research, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

In-situ and ex-situ selective catalysis of biochar-based catalysts for the production of high-quality bio-oil and H2-rich gas from tobacco stem - Xin Tang; Xiang Yang Li; Qiu Fa He; Yao Peng; Bin Peng; Yu Zhang; Wei Luo; Zhi Zhou (Journal of Environmental Chemical Engineering, 2024)

Monomethyl branched-chain fatty acids—a pearl dropped in the ocean - Yuan He; Jing-Nan Lei; Shuang Zhu; Yuan-Fa Liu; Yong-Jiang Xu (Critical Reviews in Food Science and Nutrition, 2024)

Characterizing the distribution pattern of traffic-related air pollutants in near-road neighborhoods - Meng-Yi Jin; John Gallagher; Xiao-Bing Li; Kai-Fa Lu; Zhong-Ren Peng; Hong-Di He (Environmental Monitoring and Assessment, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Auto-mmBCFAs: A swift precision approach for determination of monomethyl branched-chain fatty acids - Yuan He; Jie Li; Jia-Chen Shi; Yuan-Fa Liu; Yong-Jiang Xu (Food Bioscience, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Influence of landform, soil properties, soil Cd pollution and rainfall on the spatial variation of Cd in rice: Contribution and pathway models based on big data - Shu-Fang Pan; Xiong-Hui Ji; Xin-Liang Liu; Yun-He Xie; Shun-Yong Xiao; Fa-Xiang Tian; Tao Xue; Sai-Hua Liu (Science of The Total Environment, 2024)

Effects of Brown Fishmeal on Growth Performance, Digestibility, and Lipid Metabolism of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Guo-Fang Zhong; Liang-Fa Zhang; Yi Zhuang; Qi Li; He Huang; Cong Cao; Zhan-Ying Zhu; Zhong-Yuan Huang; Nu-An Wang; Kun Yuan (Marine Biotechnology, 2024)

Global impacts of vegetation clumping on regulating land surface heat fluxes - Fa Li; Dalei Hao; Qing Zhu; Kunxiaojia Yuan; Renato K. Braghiere; Liming He; Xiangzhong Luo; Shanshan Wei; William J. Riley; Yelu Zeng; Min Chen (Agricultural and Forest Meteorology, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

New nornemoralisin and nemoralisin diterpenoids from Aphanamixis polystachya - Yan-Wu Chen; Shi-Li Wu; Fa-Wu Dong; Hua-Yi Jiang; Hong-Ping He (Phytochemistry Letters, 2023)

In vivo antibacterial activity of medicinal plant Sophora flavescens against Streptococcus agalactiae infection - Fa‐Li Zhang; Liu Yang; Wei‐Hao He; Ling‐Jun Xie; Fei Yang; Ying‐Hui Wang; Ai‐Guo Huang (Journal of Fish Diseases, 2023)
Streptococcosis disease caused by Streptococcus agalactiae (Group B Streptococcus, GBS) results in a huge economic loss of tilapia culture. It is urgent to find new antimicrobial agents against streptococcosis. In this study, 20 medicinal plants were evaluated in vitro and in vivo to obtain medicinal plants and potential bioactive compounds against GBS infection. The results showed that the ethanol extracts of 20 medicinal plants had low or no antibacterial properties in vitro, with a minimal inhibitory concentration ≥256 mg/L. Interestingly, in vivo tests showed that 7 medicinal plants could significantly inhibit GBS infection in tilapia, and Sophora flavescens (SF) had the strongest anti‐GBS activity in tilapia, reaching 92.68%. SF could significantly reduce the bacterial loads of GBS in different tissues (liver, spleen and brain) of tilapia after treated with different tested concentrations (12.5, 25.0, 50.0 and 100.0 mg/kg) for 24 h. Moreover, 50 mg/kg SF could significantly improve the survival rate of GBS‐infected tilapia by inhibiting GBS replication. Furthermore, the expression of antioxidant gene cat , immune‐related gene c‐type lysozyme and anti‐inflammatory cytokine il‐10 in liver tissue of GBS‐infected tilapia significantly increased after treated with SF for 24 h. Meanwhile, SF significantly reduced the expression of immune‐related gene myd88 and pro‐inflammatory cytokines il‐8 and il‐1β in liver tissue of GBS‐infected tilapia. The negative and positive models of UPLC‐QE‐MS, respectively, identified 27 and 57 components of SF. The major components of SF extract in the negative model were α, α‐trehalose, DL‐malic acid, D‐ (−)‐fructose and xanthohumol, while in the positive model were oxymatrine, formononetin, (−)‐maackiain and xanthohumol. Interestingly, oxymatrine and xanthohumol could significantly inhibit GBS infection in tilapia. Taken together, these results suggest that SF can inhibit GBS infection in tilapia, and it has potential for the development of anti‐GBS agents.

Quantifying traffic-related carbon emissions on elevated roads through on-road measurements - Dan-Ni Lu; Hong-Di He; Hong-Mei Zhao; Kai-Fa Lu; Zhong-Ren Peng; Jian Li (Environmental Research, 2023)

A novel cerium organic network modified graphene oxide prepared multifunctional waterborne epoxy-based coating with excellent mechanical and passive/active anti-corrosion properties - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Pan Liu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

Assessment and prevention on the potential rockfall hazard of high-steep rock slope: a case study of Zhongyuntai mountain in Lianyungang, China - Zhong-Min Ji; Tian-Li Chen; Fa-Quan Wu; Zhen-Hua Li; Qing-He Niu; Ke-Yi Wang (Natural Hazards, 2023)

Vegetation clumping modulates global photosynthesis through adjusting canopy light environment - Fa Li; Dalei Hao; Qing Zhu; Kunxiaojia Yuan; Renato K. Braghiere; Liming He; Xiangzhong Luo; Shanshan Wei; William J. Riley; Yelu Zeng; Min Chen (Global Change Biology, 2023)
The spatial dispersion of photoelements within a vegetation canopy, quantified by the clumping index (CI), directly regulates the within‐canopy light environment and photosynthesis rate, but is not commonly implemented in terrestrial biosphere models to estimate the ecosystem carbon cycle. A few global CI products have been developed recently with remote sensing measurements, making it possible to examine the global impacts of CI. This study deployed CI in the radiative transfer scheme of the Community Land Model version 5 (CLM5) and used the revised CLM5 to quantitatively evaluate the extent to which CI can affect canopy absorbed radiation and gross primary production (GPP), and for the first time, considering the uncertainty and seasonal variation of CI with multiple remote sensing products. Compared to the results without considering the CI impact, the revised CLM5 estimated that sunlit canopy absorbed up to 9%–15% and 23%–34% less direct and diffuse radiation, respectively, while shaded canopy absorbed 3%–18% more diffuse radiation across different biome types. The CI impacts on canopy light conditions included changes in canopy light absorption, and sunlit–shaded leaf area fraction related to nitrogen distribution and thus the maximum rate of Rubisco carboxylase activity ( V cmax ), which together decreased photosynthesis in sunlit canopy by 5.9–7.2 PgC year −1 while enhanced photosynthesis by 6.9–8.2 PgC year −1 in shaded canopy. With higher light use efficiency of shaded leaves, shaded canopy increased photosynthesis compensated and exceeded the lost photosynthesis in sunlit canopy, resulting in 1.0 ± 0.12 PgC year −1 net increase in GPP. The uncertainty of GPP due to the different input CI datasets was much larger than that caused by CI seasonal variations, and was up to 50% of the magnitude of GPP interannual variations in the tropical regions. This study highlights the necessity of considering the impacts of CI and its uncertainty in terrestrial biosphere models.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Experimental study on the suffusion mechanism of gap-graded soils under an exceedance hydraulic gradient - Liang Chen; Yu Wan; Jian-Jian He; Chun-Mu Luo; Shu-Fa Yan; Xian-Feng He (Natural Hazards, 2021)

Cyclometalated Ru(II) β-carboline complexes induce cell cycle arrest and apoptosis in human HeLa cervical cancer cells via suppressing ERK and Akt signaling - Jincan Chen; Yuanyuan Deng; Jie Wang; Suxiang Chen; Fa Peng; Xuerong He; Meijun Liu; Hui Luo; Jingjing Zhang; Lanmei Chen (JBIC Journal of Biological Inorganic Chemistry, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Surface fractal dimensions as a characterization parameter for methane adsorption–induced coal strains - Jie Zhu; Yang Zhang; Rui Zhang; Bo Zhang; Jun Tang; Fa He (Arabian Journal of Geosciences, 2020)

Risk profiling using metabolomic characteristics for susceptible individuals of drug-induced liver injury caused by Polygonum multiflorum - Le Zhang; Ming Niu; Ai-wu Wei; Jin-fa Tang; Can Tu; Zhao-fang Bai; Zheng-sheng Zou; Xiao-he Xiao; You-ping Liu; Jia-bo Wang (Archives of Toxicology, 2020)

3D inversion modeling of joint gravity and magnetic data based on a sinusoidal correlation constraint - Xiu-He Gao; Sheng-Qing Xiong; Zhao-Fa Zeng; Chang-Chun Yu; Gui-Bin Zhang; Si-Yuan Sun (Applied Geophysics, 2019)

Effects of seasonal water-level fluctuation on soil pore structure in the Three Gorges Reservoir, China - Shu-juan Zhang; Qiang Tang; Yu-hai Bao; Xiu-bin He; Feng-xia Tian; Fa-you Lü; Ming-feng Wang; Raheel Anjum (Journal of Mountain Science, 2018)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Fibroblast proliferation alters cardiac excitation conduction and contraction: a computational study - He-qing Zhan; Ling Xia; Guo-fa Shou; Yun-liang Zang; Feng Liu; Stuart Crozier (Journal of Zhejiang University-SCIENCE B, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Lysinibacillus mangiferahumi sp. nov., a new bacterium producing nematicidal volatiles - Ling-Ling Yang; Ying Huang; Jie Liu; Li Ma; Ming-He Mo; Wen-Jun Li; Fa-Xiang Yang (Antonie van Leeuwenhoek, 2012)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

Fluid sensitivity study of elastic parameters in low-medium porosity and permeability reservoir rocks - Fa-Gen Pei; Chang-Chun Zou; Tao He; Ge Shi; Gen-Gen Qiu; Ke-Ying Ren (Applied Geophysics, 2010)

Enhancive effect of N,N′-dinitrosopiperazine on inducing precancerous lesion on nasal and/or nasopharyngeal epithelia of TgN(p53mt-LMP1)/HT mice - Dao-fa Tian; Ying-chun He; Fang-guo Lu; Fa-qing Tang (Journal of Zhejiang University-SCIENCE B, 2009)

Study on ambient air quality in Beijing for the summer 2008 Olympic Games - Wen-xing Wang; Fa-he Chai; Kai Zhang; Shu-lan Wang; Yi-zhen Chen; Xue-zhong Wang; Ya-qin Yang (Air Quality, Atmosphere & Health, 2008)

Biocatalytic resolution of glycidyl aryl ethers by Trichosporon loubierii: cell/substrate ratio influences the optical purity of (R)-epoxides - Yi Xu; Jian-He Xu; Jiang Pan; Yan-Fa Tang (Biotechnology Letters, 2004)

The occurrence of leafminers and their parasitoids on vegetables and weeds in Hangzhou area, Southeast China - Xue-xin Chen; Fa-yong Lang; Zhi-hong Xu; Jun-hua He; Yun Ma (BioControl, 2003)

Structural studies of the glycopeptides of B-chain of cinnamomin – a type II ribosome-inactivating protein by nuclear magnetic resonance - Zheng Pu; Yiming Li; Fa-jian Hou; Fahu He; Naixia Zhang; Houming Wu; Wang-Yi Liu (Glycoconjugate Journal, 2000)

Pheromone Components in the Larch Bark Beetle, Ips cembrae, from China: Quantitative Variation among Attack Phases and Individuals - Qing-He Zhang; Göran Birgersson; Fredrik Schlyter; Guo-Fa Chen (Journal of Chemical Ecology, 2000)